(3GdJWhjQ GdJfXjej (B:s (3eONd JMdjdj ddeaGgje h GdYdGbGJ ,GdGSJQGJjLjGJ h GdYedjGJ , GdefGgL h GdJbfjGJ (B/s - (3GdZGdHj, WGgQ eMSfs; (3UGdM, GMeO Ydj s ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3GdGWGQ GdeaGgjej ddJWhQ GdJfXjej h efWdbGJg GdGSGSjI , YdGbI GdJWhjQ GdJfXjej HGdJMhd GdJfXjej h bjeg h CNdGbjGJg h HYGde GdGOGQI h GdbjGOI GdJMhjdjI h fJGFLgG , GOGQI GdJWhjQ GdJfXjej h GSJQGJjLjGJg h cPdc YedjGJ gPG GdJWhjQ h Jbhje HQGeLg , eaghe efGgL GdJWhjQ GdJfXjej h eLGdGJgG h CfhGYgG h CNjQG eaghe JbfjGJ GdJWhjQ GdJfXjej h CSS JUfjagG h GSJNOGeGJgG (B.s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3GdGOGQIs; (3GdJNWjWs; (3GdJfXjes